Principles of Entrepreneurship (ENT530): Business Model Canvas: Cobeads / Ainul Mardhiha Azhar … [et al.] - Azhar, Ainul Mardhiha; Sofyan, Audy Agil; Saiful Anwar, Izz Iqbal; Kamarulzaman, Karisma Durar; Kamarudin, Nur Athirah; Azman, Nur Azhani (2021)
BioTech Sdn Bhd is a new company engaged in health technology to support the acceleration of solutions for every global health problem. With a vision to become a trustworthy health technology company that prioritizes quality and impact on people, our mission is to focus on developing the latest product innovations to achieve global health. The COVID-19 pandemic that has occurred in all countries in the world has forced us to innovate to make a product that is very useful to support efforts to accelerate the process of stopping the spread of the virus. The products we make are the answer to what the world needs today, namely COBEADS. COBEADS is a product that functions as a social distance detection bracelet that warns us when we are less than 2 meters away to avoid physical contact with strangers who we don't know their medical history for. COBEADS works with the help of an infrared camera that functions as a body temperature detector and recognizes a person through artificial intelligence that is connected to a smartphone application which will later be very useful for the tracing process. COBEADS will issue an alert in the form of sound or vibration that can be adjusted when in a crowd or near strangers who are not family members which will later be registered in the smartphone application. The World Health Organization (WHO) stated that there was a need for mutual awareness to take care of each other in order to avoid this virus. With our product, COBEADS which will assist in controlling a safe distance so that prevention efforts can be carried out effectively. With a bracelet that is fashionable and can be used by anyone, we project that everyone can use our products, especially for people who have high mobility who have to work or go out because it is a high risk for people who constantly meet with many people.